Three-dimensional rock slope stability analysis considering the surface load distribution. Issue 8 (13th September 2016) - Lin, Hang; Zhong, Wenwen; Cao, Ping
Abstract : Previous studies on slope stability mainly focused on conditions under gravity load in which the slope tends to slide down along the potential slip surface. However, the existence of a horizontal load on the slope surface can restrain the slope-slipping trend and improve the stability of the slope, similar to the effect of a retaining wall. The slope failure mode can be altered by a sufficiently large horizontal surface load. In this case, the slope stability problem will be converted to a rock foundation stability problem. However, the reciprocal transformation of slope stability and rock foundation stability has been rarely studied. This study considers the Ice and Snow World project in Changsha, China, as the engineering background. This project is located at an abandoned mine pit, the structural load of which mainly acts on the top of the pit. To study the three-dimensional (3D) slope stability under the slope surface load, a 3D slope model is established using the numerical commercial code. The mechanical parameters of the rock mass, as well as the value and the distribution areas of the surface load, are changed to identify the corresponding safety factor of rock mass, deformation and failure mode.